2014
DOI: 10.1002/etc.2697
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐silicon dioxide mitigates the adverse effects of salt stress on Cucurbita pepo L

Abstract: Research into nanotechnology, an emerging science, has advanced in almost all fields of technology. The aim of the present study was to evaluate the role of nano-silicon dioxide (nano-SiO2 ) in plant resistance to salt stress through improvement of the antioxidant system of squash (Cucurbita pepo L. cv. white bush marrow). Seeds treated with NaCl showed reduced germination percentage, vigor, length, and fresh and dry weights of the roots and shoots. However, nano-SiO2 improved seed germination and growth chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(154 citation statements)
references
References 40 publications
(52 reference statements)
17
137
0
Order By: Relevance
“…Hussein et al [27] affirmed that addition of nano-SiO 2 to salt stressed tomato improved leaf proline accumulation. Similar results in squash were reported by [28] as well. Moreover, the use of ZnO.Fe 3 O 4 was reported to increase proline contents in Moringa peregrina under salinity [81].…”
Section: Impacts Of Soil Salinity On Leaf Proline Gibberellic Acid Asupporting
confidence: 91%
“…Hussein et al [27] affirmed that addition of nano-SiO 2 to salt stressed tomato improved leaf proline accumulation. Similar results in squash were reported by [28] as well. Moreover, the use of ZnO.Fe 3 O 4 was reported to increase proline contents in Moringa peregrina under salinity [81].…”
Section: Impacts Of Soil Salinity On Leaf Proline Gibberellic Acid Asupporting
confidence: 91%
“…In other studies the application of Si-NPs increased the rate of photosynthesis, mesophyll conductance and plant water use efficiency of plants under saline stress (Tuna et al, 2008;Haghighi and Pessarakli, 2013;Almutari, 2016). In previous reports, the identical alleviation of the adverse effects of salt stress was also observed with SiO 2 -NPs treatment with reduced degradation of chlorophyll and increased net photosynthetic rate, stomatal conductance, transpiration rate, and water use efficiency (Siddiqui et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Application of silicon decreased activities of antioxidant enzymes under salinity stress; this is associated with decreasing of electrolyte leakage, ROS synthesis and H 2 O 2 contents (Siddiqui et al, 2014 andShahid et al, 2015). More or fewer data were reported by Abbas et al (2015) that foliar application of silicon (150 mgL −1 ), decreased lipid peroxidation and increased antioxidant enzymes activities in both leaves and root of okra under salt stress.Similar studies showed that siliconmediated enhancement in antioxidant enzyme activities and decreased in oxidative stress in saltstressed tomato plants grown in sand culture (Li et al, 2015).…”
Section: Antioxidant Defense Systemmentioning
confidence: 94%